Purification of calcium fluoride (CaF2) sludge by selective carbonation of gypsum. Issue 1 (February 2021) - Takaya, Yutaro; Inoue, Shota; Kato, Tatsuya; Fuchida, Shigeshi; Tsujimoto, Susumu; Tokoro, Chiharu
Graphical abstract: Highlights: A new technique for the removal of sulfate (gypsum) from CaF2 sludge is proposed. Shrinking core model can account for the dissolution kinetics of gypsum and fluorite. Gypsum in CaF2 sludge was selectively carbonated in Na2 CO3 solution. Sulfate content in CaF2 sludge easily decreased under 1 % with the proposed method. Abstract: Reusing wastewater and sludge containing CaF2 has become important for ensuring a stable supply of fluorine resources. Because sulfate in CaF2 resources causes equipment corrosion, an effective technique for sulfate removal from CaF2 resources is critically needed for CaF2 sludge reuse. In this study, we proposed a new technique for the purification of CaF2 sludge by selectively carbonating sulfate contaminants (mainly gypsum). First, we demonstrated the dissolution of gypsum and fluorite in Na2 CO3 solution and examined the dissolution kinetics by adapting a shrinking core model. In both cases, the rate limiting factor for the dissolution phenomenon changed from a dissolution to a diffusion reaction after only a few minutes. Additionally, the diffusion rate constant for fluorite was 500, 000 times slower than that for gypsum because of the textural differences of the formed calcite. Then, sulfate removal experiments with the gypsum-fluorite mixed sludge sample with Na2 CO3 solution were conducted. In these experiments, we confirmed that almost all of the gypsum was selectively replaced by CaCO3 and that the gypsum content in the sludge sample decreased from 21.2% to 0.8% in 180 min at 75 °C without any loss of fluorite. Therefore, we concluded that selective carbonation is an effective purification technique for sulfate containing CaF2 sludge.